Expression and significance of FXYD-3 protein in gastric adenocarcinoma - Zhu, Zhen-Long; Zhao, Zeng-Ren; Zhang, Yu; Yang, Yan-Hong; Wang, Zheng-Min; Cui, Dong-Sheng; Wang, Ming-Wei; Kleeff, Jörg; Kayed, Hany; Yan, Bao-Yong; Sun, Xiao-Feng (Disease markers, 2010)
Objective: FXYD-3, also known as Mat-8, is a member of the FXYD protein family. It was reported that this protein can associate with and modify the transport properties of Na, K-ATPase, and may play an important role in a variety of physiological and pathological states. This protein is up-regulated in certain types of cancers (such as breast, prostate and pancreatic cancer), but down-regulated in other types of cancers (such as colon and kidney cancer). No study has been performed in gastric cancer; therefore, the aim of this project was to investigate FXYD-3 expression and its clinicopathological significance in gastric adenocarcinoma.Patients and methods: FXYD-3 protein was examined by immunohistochemistry in normal gastric mucous (n = 29) and gastric adenocarcinoma (n = 51), obtained from surgical resection of gastric cancer patients.Results: FXYD-3 protein was present in the cytoplasm of normal gastric epithelial cells or gastric cancer cells. The rate of FXYD-3 strong expression was significantly higher in cancer (51% of 51) than in normal mucosa (10% of 29, X2=13.210, p < 0.0001). FXYD-3 expressed strongly in ulcerative/infiltrating types of cancers compared to polypoid/fungating ones (X2 = 5.765, p = 0.016). However, FXYD-3 expression was not correlated with patient’s gender, age, tumor size, lymph node status and histological grade (p > 0.05).Conclosion: Up-regulated expression of FXYD-3 protein may be involved in tumourgenesis and invasion of gastric adenocarcinoma.